2016
DOI: 10.14740/jocmr2525w
|View full text |Cite
|
Sign up to set email alerts
|

Association BetweenToxoplasma gondiiExposure and Heart Disease: A Case-Control Study

Abstract: BackgroundThe parasite Toxoplasma gondii causes infections all around the world. Infections with T. gondii are systemic and the parasite can persist in the heart muscle. Very little is known about the impact of T. gondii on patients with heart disease. We determined the association between T. gondii exposure and patients suffering from heart diseases attending in a public hospital in Durango, Mexico; the association of T. gondii exposure with socio-demographic, behavioral, and clinical characteristics of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 27 publications
5
15
2
Order By: Relevance
“…Seropositivity to T . gondii was associated with alcohol consumption in patients with heart disease [ 14 ]. In two studies of decedents in Poland, researchers found a positive association between T .…”
Section: Introductionmentioning
confidence: 99%
“…Seropositivity to T . gondii was associated with alcohol consumption in patients with heart disease [ 14 ]. In two studies of decedents in Poland, researchers found a positive association between T .…”
Section: Introductionmentioning
confidence: 99%
“…Toxoplasma gondii is an obligate intracellular protozoan parasite estimated to have infected one‐third of the world population (Pappas et al ; Alvarado‐Esquivel et al , ; Hill and Dubey, ). Toxoplasma is mainly acquired through consumption of undercooked meat from infected animals or by ingestion of environmental oocysts that are shed in the feces of infected felines, the definitive host.…”
Section: Introductionmentioning
confidence: 99%
“… 3 However, individuals who develop toxoplasmosis, the disease caused by T. gondii , may present several well-recognized clinical features: lymphadenopathy, chorioretinitis, and meningoencephalitis. 4 , 5 In addition, infection with T. gondii has been associated with heart disease, 6 , 7 schizophrenia, 8 , 9 depression, 10 , 11 and mixed anxiety and depression. 12 Immunocompromised individuals infected with T. gondii may develop disseminated and life-threatening disease.…”
Section: Introductionmentioning
confidence: 99%